2019
DOI: 10.1155/2019/8718795
|View full text |Cite
|
Sign up to set email alerts
|

Association ofADRB2rs1042713 with Obesity and Obesity-Related Phenotypes and Its Interaction with Dietary Fat in Modulating Glycaemic Indices in Malaysian Adults

Abstract: Gene-diet interaction studies have reported that individual variations in phenotypic traits may be due to variations in individual diet. Our study aimed to evaluate (i) the association of ADRB2 rs1042713 with obesity and obesity-related metabolic parameters and (ii) the effect of dietary nutrients on these associations in Malaysian adults. ADRB2 genotyping, dietary, physical activity, anthropometric, and biochemical data were collected from 79 obese and 99 nonobese individuals. Logistic regression revealed no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In the present study, we did not find any significant interaction between different types of RMRs across PUFA categories. It has previously been shown that the higher intake of PUFA is beneficial for glycemic indices and lipid profile among individuals who carried G allele of ADRB2 rs1042713 polymorphism [ 60 ]. Moreover, a meta-analysis on feeding trials revealed that PUFA had some effect in improving insulin resistance [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we did not find any significant interaction between different types of RMRs across PUFA categories. It has previously been shown that the higher intake of PUFA is beneficial for glycemic indices and lipid profile among individuals who carried G allele of ADRB2 rs1042713 polymorphism [ 60 ]. Moreover, a meta-analysis on feeding trials revealed that PUFA had some effect in improving insulin resistance [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the 2-gene signature, ADRB2 is a protein coding gene encoding the beta2 adrenergic receptor that belongs to a member of the G protein-coupled receptor (GPCR) superfamily. Many studies have confirmed that several diseases such as asthma ( 72 ), obesity ( 73 ) and type 2 diabetes ( 74 ) were associated with ADRB2 . Recently, researchers have found that ADRB2 was significantly correlated with various aspects related to cancer such as prostate cancer ( 75 ) and breast cancer ( 74 ), which indicates that ADRB2 is related to cell proliferation and apoptosis, tumor growth and metastasis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we did not nd any signi cant interaction between different types of RMRs across PUFA categories. It has previously been shown that the higher intake of PUFA is bene cial for glycemic indices and lipid pro le among individuals who carried G allele (60). Moreover, a meta-analysis on feeding trials revealed that PUFA had some effect in improving insulin resistance (61).…”
Section: Discussionmentioning
confidence: 99%